Effects of Sodium Butyrate Treatment on Histone Modifications and the Expression of Genes Related to Epigenetic Regulatory Mechanisms and Immune Response in European Sea Bass (Dicentrarchus Labrax) Fed a Plant-Based Diet - Terova, Genciana (PLoS One, 2016)
Bacteria that inhabit the epithelium of the animals’ digestive tract provide the essential biochemical pathways for fermenting otherwise indigestible dietary fibers, leading to the production of short-chain fatty acids (SCFAs). Of the major SCFAs, butyrate has received particular attention due to its numerous positive effects on the health of the intestinal tract and peripheral tissues. The mechanisms of action of this four-carbon chain organic acid are different; many of these are related to its potent regulatory effect on gene expression since butyrate is a histone deacetylase inhibitor that play a predominant role in the epigenetic regulation of gene expression and cell function. In the present work, we investigated in the European sea bass (Dicentrarchus labrax) the effects of butyrate used as a feed additive on fish epigenetics as well as its regulatory role in mucosal protection and immune homeostasis through impact on gene expression. Seven target genes related to inflammatory response and reinforcement of the epithelial defense barrier [tnfα (tumor necrosis factor alpha) il1β, (interleukin 1beta), il-6, il-8, il-10, and muc2 (mucin 2)] and five target genes related to epigenetic modifications [dicer1(double-stranded RNA-specific endoribonuclease), ehmt2 (euchromatic histone-lysine-N-methyltransferase 2), pcgf2 (polycomb group ring finger 2), hdac11 (histone deacetylase-11), and jarid2a (jumonji)] were analyzed in fish intestine and liver. We also investigated the effect of dietary butyrate supplementation on histone acetylation, by performing an immunoblotting analysis on liver core histone extracts. Results of the eight-week-long feeding trial showed no significant differences in weight gain or SGR (specific growth rate) of sea bass that received 0.2% sodium butyrate supplementation in the diet in comparison to control fish that received a diet without Na-butyrate. Dietary butyrate led to a twofold increase in the acetylation level of histone H4 at lysine 8, but showed no effect on the histone H3 at Lys9. Moreover, two different isoforms of histone H3 that might correspond to the H3.1 and H3.2 isoforms previously found in terrestrial animals were separated on the immunoblots. The expression of four (il1 β, il8, irf1, and tnfα) out of seven analyzed genes related to mucosal protection and inflammatory response was significantly different between the two analyzed tissues but only il10 showed differences in expression due to the interaction between tissue and butyrate treatment. In addition, butyrate caused significant changes in vivo in the expression of genes related to epigenetic regulatory mechanisms such as hdac11, ehmt2, and dicer1. Statistical analysis by two-way ANOVA for these genes showed not only significant differences due to the butyrate treatment, but also due to the interaction between tissue and treatment.